A escola especial no contexto da educação inclusiva e da globalização - Cardias, Sibele Macagnan (2007)
This work approaches the theme of Special School taking into account Inclusive Education and Globalization and aims to clarify teacher=s conceptions regarding special school abreast of the Inclusion Paradigm. Considering the nowadays society scenery, characterized by an immense diversity, the focus of this research refer to the services offered by special education and that have been criticized in face of the possibility of an inclusive education able to guarantee access to everyone in a plural and democratic environment and, though, less segragative. Thus we tried to build analysis and reflexion spaces through the development of meetings in a focal group constituted of teachers of the Deputy Carlos Santos State Special School B CIEP, located in the city of Cruz Alta, Rio Grande do Sul state. The collecting of data was orientated by the theoretical basis of the Focal Group Technic and with questionnaires as complemental collecting instruments. During the meetings themes relating to Globalization, Neoliberalism, Special Education, Special School and Inclusive Education, which constituted the research categories, wer discussed. The collected data was analysed using the Content Analysis Method as a way of understanding the construction of what the teachers meant in their talks in relation to the research theme. Based on this study, and not aiming to bring it to an end, but otherwise pointing to new challenges for this research area, it is concluded that the special school still needs to have its space protected in a globalized and exclusivist society, since there exist subjects who need this service in order to better develop their potentialities. It was also inferred that the role of the school, both special or regular, needs constant reflexion to offer a real better quality education